Stroke Templates and Trainee Education are Associated With Improved Data Capture in an Academic Hospital. Issue 2 (March 2020) - Toumbs, Randi; Dao, Thanh; Zhu, Liang; McCullough, Louise; Savitz, Sean; Cossey, TC
ABSTRACT: Background: Effective medical record documentation is required to support accurate capture of diagnoses, patient acuity (case mix index [CMI]), and justify resource utilization for reimbursement. Billing code complexity and a lack of formal documentation education in training programs have created a need for academic medical centers to incorporate training for trainees (residents, fellows, and new nurse practitioners). We hypothesized that standardized stroke note templates, trainee education, and feedback from chart audits would improve documentation accuracy. Purpose: To improve the accurate/complete capture of expected (E) length of stay (LOS) and CMI by designing/implementing ischemic and hemorrhagic stroke templates containing high-frequency complication and comorbidity diagnoses with the greatest impact on stroke populations, combined with trainee education and chart audits. Methods: Descriptive statistics were used for outcomes before/after implementation of the templates. Primary outcomes include ELOS and CMI. Wilcoxon rank-sum test or chi-square test was used for group comparison. Results: The post-template group demonstrated a significant improvement in ELOS from 5.84 to 8.27 days ( p < .0001). Case mix index increased (1.73–1.75; p < .0001) in the post-template group. Conclusions: Stroke-specific templates, trainee education, and chart audits were associated with significant improvement in documentation accuracy and an improved business model of stroke care in our hospital. Abstract : Supplemental Digital Content is Available in the Text.